Non‐alcoholic fatty liver disease: a review of epidemiology, risk factors, diagnosis and management. Issue 9 (14th September 2020) - Huang, Tony (Dazhong); Behary, Jason; Zekry, Amany
Abstract: Due to the rising prevalence of obesity and type II diabetes mellitus, non‐alcoholic fatty liver disease is becoming the leading cause of chronic liver disease in the Western world. In some patients, simple steatosis can result in non‐alcoholic steatohepatitis which over time can lead to liver cirrhosis and its associated sequelae, including hepatocellular carcinoma. Early identification and management of patients at risk with intensive dietary and lifestyle modification are essential to prevent the development of advanced liver disease and its complications. In this review, we will discuss the epidemiology of non‐alcoholic fatty liver disease, pathogenesis, diagnosis, management and surveillance strategies to offset the morbidity and mortality of this disease, as well as liver and non‐liver‐related complications.